Improved treatment of vulvovaginal candidiasis with Clotrimazole plus probiotic Lacidophilin Vaginal Capsules: A prospective, real-world study. Issue 1 (6th January 2023) - Zeng, Xianling; An, Ruifang; Li, Han; Zhang, Yafei
Abstract : Background: Clotrimazole has long been used to treat vulvovaginal candidiasis (VVC), yet the antibiotic resistance, adverse effects and recurrences still bring about a great challenge for the clinicians. To explore the effect of probiotic Lacidophilin Vaginal Capsules plus Clotrimazole Vaginal Tablets (500mg) in the treatment of uncomplicated VVC, a self-controlled real-world study was conducted. Methods: Twenty-seven women with a normal vaginal flora and 15 women with uncomplicated VVC were recruited. The patients were treated with the single dose of Clotrimazole Vaginal Tablets (500mg) supplemented with 2 Lacidophilin Vaginal Capsules for the following 7 days. The patients were prospectively examined 4 times and the time points were at m0 (the first visit), m1 (8–10 days after the first visit), m2 (30 days after the second visit) and m3 (30 days after the third visit). However, women in the healthy normal control group were examined just once at the first visit. The obtained vaginal secretions were examined by high-throughput sequencing. Results: The mean age in healthy control group and case group was 28.63 ± 5.40y and 27.67 ± 3.33y, respectively. Finally, 46.67% (7/15) of patients were cured at the second visit, 61.54% (8/13) were cured at the third visit and eventually 72.73% (8/11) were cured. A total of 81 samples were sequenced, generating 1668 operation taxonomy units among all the samples. The bacterial composition of women in the healthy control group was exceedingly abundant and dominated by Lactobacillus, especially by Lactobacillus. crispatus, and followed by Lactobacillus. iners, Lactobacillus. jensenii and Gardneralla. On the contrary, the bacterial composition of women with VVC was relatively few and dominated by Lactobacillus. iners. During the process of treatment, the bacterial abundance of VVC patients was increased gradually. At the final visit, the abundance of vaginal flora was augmented further with the dominant bacteria being Lactobacillus. crispatus, followed by Lactobacillus. iners. Conclusion: Clotrimazole Vaginal Tablets plus probiotic Lacidophilin Vaginal Capsules could improve the effect in treating uncomplicated VVC. This improved effect was achieved perhaps through improving the composition of vaginal flora and restoring vaginal microecology.